A comunidade fitoplanctônica como bioindicadora da qualidade da água para a saúde pública e ambiental: o caso da Costa Norte do Município de Raposa - Maranhão - SANTOS, Nágela Gardênia Rodrigues dos (2018)
In aquatic environments, the phytoplankton community forms the basis of the food chain and the impacts may interfere with its composition. The aim of this study is to characterize the phytoplankton community and environmental variables in areas of the northern coast of the municipality of Raposa, with emphasis on the investigation of potentially toxic and / or harmful bioindicator species for human and aquatic health. Sixty samples of the microphytoplankton obtained in six samples were analyzed in two seasonal periods (rainy and dry season) in quadrature tide in the flood. Health Geography approaches were used for spatiotemporal analyzes in order to answer questions related to health and its correlations with the environment, as well as statistical analyzes of the data. The diatoms were the ones that contributed the most to the local microphytoplankton richness, being responsible for 82.05% of the identified taxa. Some are considered to be potentially harmful in the literature, especially the genera Asterionellopsis, Chaetoceros, Neocalyptrella, Pseudosolenia, Rhizosolonia and Skeletonema, which are associated with mechanical damage to the gills of filtering organisms, as well as the species Leptocylindrus danicus and Leptocylindrus mininus framed as potentially harmful. The specific diversity indexes indicated that the phytoplankton community had a significant increase in the rainy season, in addition to having shown a uniform phycoforge (0.53 to 0.93) of the values of equitability. Regarding the analyzes of Normality and Homogeneity Test and One-Way ANOVA, showed that salinity, density, secchi, water temperature and pH presented normal and heterogeneous values showing that there was significant difference of values of environmental variables in relation to seasonality. In the analysis of Pearson's correlation, dissolved oxygen was strongly correlated with three environmental variables, temperature (R = 0.90518, p <0.05), salinity (R = 0.86178, p <0.05) and turbidity (R = 0.8155, p <0.05). By means of the Principal Components Analysis (PCA), the first two factors explained 51.30% of the variations occurring in the environment, and factor 1 explained 33.94%, factor 2 justified 17.36% of the data variation. The correlation values were estimated from the "p" of significance higher than 0.05 for the percentage of strong relation, with values above 0.5 showing a well defined seasonal scenario in relation to the environmental variables. The Canonic Correspondence Analysis (CCA), not rectified for the dry season, explained 91.46% of the relationships between species and environmental variables, while for the rainyseason the CCA summarized 82.99%. The average age of fishermen interviewed was 51, married, with 2 to 4 children. However, most had incomplete secondary education, which was justified because of the need to work to support the family early. The fishermen attribute the lack of fishing resources, the exaggerated increase of fishermen, often of irregular form in our Maranhão Coast, fishermen that comes from other states like Ceará and Pará, with a structure better than the one that they have and still own more elaborate gear. As for the perception of the interviewees regarding the environmental quality of the municipality of Raposa, as well as of the water masses, it is notorious the lack of basic sanitation and the amount of garbage conditioned in the mangrove banks and around the stilts. Despite improvements apparent today in the municipality of Raposa / MA, basic sanitation is still a reality to be achieved and improved. In this way, social indicators can be considered as operational tools for monitoring social reality, which will subsidize the planning and decisions of public policies.